Laparoscopic Gastric Mobilization Reduces Postoperative Mortality After Esophageal Cancer Surgery: A French Nationwide Study. Issue 5 (November 2015) - Messager, Mathieu; Pasquer, Arnaud; Duhamel, Alain; Caranhac, Gilbert; Piessen, Guillaume; Mariette, Christophe
Abstract : Objective: This study was designed to investigate the impact of laparoscopic gastric mobilization (LGM) on 30-day postoperative mortality (POM) after surgery for esophageal cancer (EC). Background: Meta-analyses of nonrandomized studies have failed to demonstrate any significant benefit of hybrid minimally invasive esophagectomy on POM, potentially due to small population samples. Moreover, none of the published randomized trials have been designed to answer this question. Methods: All consecutive patients who underwent EC resection between 2010 and 2012 in France were included in this nationwide study (n = 3009). Data were extracted from the French National Health Service Database with internal and external quality controls. Patients treated with LGM (LGM group, n = 663) were compared with those treated with open approach (open group, n = 2346). Propensity score matching and multivariable analyses were used to compensate for the differences in baseline characteristics. Results: The 30-day POM rate was 5.2%, significantly lower after LGM, compared with open surgery (3.3% vs 5.7%, P = 0.005), as well as in-hospital (5.6% vs 8.1%, P = 0.028), and 90-day POM (6.9% vs 10.0%, P = 0.016). After propensity score matching, 30-day POM rates were 3.3% versus 5.9%, respectively ( P = 0.029). By multivariable analysis, age ≥60 years, malnutrition and cardiovascular comorbidity were independently associated with higher POM, whereas LGM was associated with a decrease in POM (OR 0.60, 95% CI 0.37–0.98, P = 0.041). Conclusions: This all-inclusive nationwide study strongly suggests that POM is significantly reduced after LGM for EC. This is high valuable evidence that helps decision making regarding the optimal approach for EC surgery.